The Spinal Control of Backward Locomotion - Harnie, Jonathan (J Neurosci, 2021)
Animal locomotion requires changing direction, from forward to backward. Here, we tested the hypothesis that sensorimotor circuits within the spinal cord generate backward locomotion and adjust it to task demands. We collected kinematic and electromyography (EMG) data during forward and backward locomotion at different treadmill speeds before and after complete spinal transection in six adult cats (three males and three females). After spinal transection, five/six cats performed backward locomotion, which required tonic somatosensory input in the form of perineal stimulation. One spinal cat performed forward locomotion but not backward locomotion while two others stepped backward but not forward. Spatiotemporal adjustments to increasing speed were similar in intact and spinal cats during backward locomotion and strategies were similar to forward locomotion, with shorter cycle and stance durations and longer stride lengths. Patterns of muscle activations, including muscle synergies, were similar for forward and backward locomotion in spinal cats. Indeed, we identified five muscle synergies that were similar during forward and backward locomotion. Lastly, spinal cats also stepped backward on a split-belt treadmill, with the left and right hindlimbs stepping at different speeds. Therefore, our results show that spinal sensorimotor circuits generate backward locomotion but require additional excitability compared with forward locomotion. Similar strategies for speed modulation and similar patterns of muscle activations and muscle synergies during forward and backward locomotion are consistent with a shared spinal locomotor network, with sensory feedback from the limbs controlling the direction. SIGNIFICANCE STATEMENT Animal locomotion requires changing direction, including forward, sideways and backward. This paper shows that the center controlling locomotion within the spinal cord can produce a backward pattern when instructed by sensory signals from the limbs. However, the spinal locomotor network requires greater excitability to produce backward locomotion compared with forward locomotion. The paper also shows that the spinal network controlling locomotion in the forward direction also controls locomotion in the backward direction.